The Evolution of WEAI and Evidence Generated: Lessons learned and future directions - Quisumbing, Agnes R. (2022)
Agnes Quisumbing SPECIAL EVENT A Decade of the Women’s Empowerment in Agriculture Index (WEAI): Lessons from Using Empowerment Metrics Co-Organized by IFPRI, United States Agency for International Development (USAID), and the Bill & Melinda Gates Foundation (BMGF) FEB 16, 2022 - 9:30 TO 11:00AM EST